Analysis of the Indonesian version of the statistical anxiety scale instrument with a psychometric approach - Iriyadi, Deni; Asdar, Ahsanul Khair; Afriadi, Bambang; Samad, Mohammad Ardani; Syaputra, Yogi Damai (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to validate the psychometric approach (using the Rasch model and confirmatory factor analysis) on the Indonesian version of the statistical anxiety scale (SAS) instrument. Sampling in this study used cluster random sampling with a total sample of 1651 which was divided into three regions of Indonesia (Western Indonesia, Central Indonesia, and Eastern Indonesia) with details of 457 males (27.46%) and 1,194 females (72.54%). The number of samples from the West Indonesia region was 922 people (55.71%), the Central Indonesia region was 605 people (36.76%), and the Eastern Indonesia region was 124 people (7.53%). The results of confirmatory factor analysis (CFA) show that the dimensions/elements of the SAS instrument meet the criteria which are then continued using the rating scale model (RSM) approach. From the results of the tests performed, it shows that all items on the SAS instrument meet the specified criteria. Thus, the SAS instrument adopted in the Indonesian context can be used to measure students’ statistical anxiety. The results of the research conducted became the initial capital to increase students’ statistical anxiety considering that statistics courses are needed in completing studies, especially quantitative research.